(untitled) (Journal of the Bangladesh Agricultural University, 2018)
The inverse relationship between farm size and productivity is one of the most debated findings in agricultural productivity researches of developing countries. Aquaculture industries of Bangladesh have been expanded tremendously but most of the aquaculture farms are small and their productivity is not as high as expected. This paper has explored the relationships among farm size, productivity and efficiency of pangas fish farms. A survey was conducted on 125 farmers by direct interviewing in Mymensingh district of Bangladesh. Stochastic frontier production function was carried out to estimates the level of technical efficiency and polynomial regression was employed to show the relationship among farm size productivity and efficiency in pangas fish farming. In general, pangas fish farming was found to be profitable, where the large size farms were more profitable than the small. Feed and salt had highly significant and positive effects on productivity, while human labor had negative influences. Larger farms were found to be more productive and technically efficient than the smaller one, and the more productive farms were found to be more efficient. These findings could be justifiable by the fact that the large size farms enjoy more financial opportunities, management and marketing facilities in commercial mode and all these facilities help them to enhance productivity and efficiency. J. Bangladesh Agril. Univ. 16(3): 513–522, December 2018